Seed Production Studies of Selected Tomato Hybrids under varied Planting Dates - MOHINDER KAUR; J.S. KANWAR (Seed Research, 2026)
Studies were conducted to assess the seed production potential of three tomato hybrids at Punjab Agricultural University during 2002-2003. Crosses of these tomato hybrids (VFN 8 x Punjab Chhuhara, ACC 8 x ACC2 and, W321 x 1-181), were made under four different planting dates viz. 20th November, 5th December, 20th December and 5th January and were evaluated for hybrid seed yield and its quality. From the investigation, it was concluded that maximum hybrid seed could be obtained from ACC 8 x ACC 2 (TH802) followed by W321 x 1-181 (TH-I) and VFN 8 x Punjab Chhuhara (TH 2312). As per dates of planting, November 20 was found to be the best planting date for obtaining highest hybrid seed yield with better seed quality. Interactions between planting dates and crosses were significant for crossed fruit weight, fruit setting (%), hybrid seed recovery and hybrid seed yield.